The Relationship Between Mental Workload and Burnout Incidences in Special School Teachers (SLB) in Surakarta City - Amalia Natasyafira; Salsabila Purnamasari (JURNAL KESMAS DAN GIZI (JKG), 2026)
Special school (SLB) teachers not only have the responsibility to teach skills and knowledge according to the characteristics and potential of their students, but they are also required to take on roles as paramedics, social workers, counselors, administrators, and therapists. The demands faced by teachers who work in special schools are far greater than those faced by teachers in regular schools. A high mental workload can reduce performance and has a significant positive effect on worker burnout. The purpose of this study was to determine the relationship between mental workload and the occurrence oof burnout among special school (SLB) teachers in Surakarta City. This study used a quantitative method with a cross-sectional research design. The study population was 176 teachers, and the sample size was calculated using the Lemeshow formula with a 95% confidence level, resulting in 121 respondents selected through proportional random sampling. Based on the results of the study, most teacher respondents have a moderate level of mental workload (47,9%) and experience moderate burnout (49,6%). The Chi-Square test shows that there is a relationship between mental workload and burnout among SLB teachers, with a p-value 0,000 (p<0.05). burnout among teachers is an issue that requires attention because they have a responsibility to create a classroom environment that supports learning. Therefore, providing support, recognition, and adequate resource is necessary to reduce the mental workload of SLB teachers and prevent burnout in order to improve occupational health